Mutually Assured Heteronomy: On the Ethics and Politics of Dialogue and Dissemination - Amit Pinchevski (Media Theory)
Setting dialogue in opposition to dissemination is one of the main themes of Speaking into the Air. This however does not entail regarding them as dichotomous or mutually exclusive. This article proposes that dialogue and dissemination are in fact interconnected, forming what I call “mutually assured heteronomy”: each finds its justification and limitation in the other. Neither autonomous nor combining to create a greater whole, dialogue and dissemination are caught in an interruptive bond. This reading allows reconsidering the ways ethics and politics are conceptualized in Speaking, revealing them as similarly linked in a non-dialectical, mutually implicating bond.